Acts of hope. James Boyd White, Acts of hope: creating authority in literature, law, and politics - P. Pether (Law Text Culture, 1997)
I approached writing this review with a measure of anxiety. James Boyd White is a friend whose encouragement and hospitality I have much reason to be grateful for. His is a generous and punctilious intellect, and as a scholar he models courteous and decent behaviour to his juniors as well as his peers. He is also without question the scholar who has thus far done most to advance interdisciplinary scholarship in law and humanities in the 'main stream' of the legal academy and the legal profession. That said, we work in different traditions: his the liberal humanist; mine the feminist poststructuralist. And so we judge and value differently. Which is to say that I disagree with many of his conclusions in this collection of essays, and almost all of the volume's assumptions and methodology. And thus that reviewing Acts of Hope in an ethical manner loomed as a knotty problem, for Boyd White's hope and my transformative politics are not two sides of the same coin, but insigne of radically different degrees of satisfaction with the present dispensation, and with those men - many of them, like Boyd White, decent, democratic, thoughtful men - who in the main speak and write the law.